Restless leg syndrome as co-morbidity in type 2 diabetes mellitus - Rajender, Akash; R., Gaurav; Kanwal, Krishna; Chaudhri, R. S.; C., Deepa; Choudhary, Priyanka; N., Mona (International Journal of Advances in Medicine, 2017)
Background: Diabetes is a global epidemic with India estimated to have the highest prevalence of 79.4 million by 2030. RLS is a common yet undiagnosed comorbidity causing significant distress. We aimed to analyze association between restless legs syndrome (RLS) and type 2 diabetes. Methods: One hundred fifty six type 2 diabetes mellitus (T2DM) and eighty eight non-diabetic controls were assessed at Mahatma Gandhi Medical College & Hospital, Jaipur, India for RLS using the international RLS study group rating scale. Several patient clinical profiles along with laboratory parameters were compared in both groups. Diabetic polyneuropathy was evaluated for its role as risk factor in diabetic RLS subjects. Results: RLS was diagnosed in 35 diabetic patients (22.44%) and in only 7 non diabetic controls (7.95%). RLS was independently associated with type 2 diabetes (P<0.04). A clinical diagnosis of polyneuropathy was made in only 22.86% of diabetic patients with comorbid RLS. In multivariate logistic regression, polyneuropathy was the only variable associated with RLS in diabetics (P<0.03). RLS manifested in diabetics after the diagnosis of diabetes was made. Conclusions: An association between RLS and type 2 diabetes is established in Indian subpopulation. In diabetic patients, polyneuropathy is the main risk factor for RLS. But, polyneuropathy only partially explains the increased prevalence of RLS in type 2 diabetics.